Crime and Mental Health Problems in Norway - a Zero-Sum Game? - Leonardsen, Dag (2019)
Through a historical overview, the author analyses the Norwegian welfare society and the limits of a social-engineering approach to social problems. While economic growth and welfare benefits expanded for many years, so did registered crime and mental problems. This paradox gives a justification for challenging established ways of thinking about social prevention policies. Since the turn of the century, crime figures have decreased while the state of mental health has worsened. The author argues that if the price of the suppression of crime is the depression of mind, then the gains are indeed pyrrhic